2009
DOI: 10.1098/rspb.2009.0003
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of evolutionary downsizing caused by selective harvest of large fish

Abstract: Evolutionary responses to the long-term exploitation of individuals from a population may include reduced growth rate, age at maturation, body size and productivity. Theoretical models suggest that these genetic changes may be slow or impossible to reverse but rigorous empirical evidence is lacking. Here, we provide the first empirical demonstration of a genetically based reversal of fishing-induced evolution. We subjected six populations of silverside fish (Menidia menidia) to three forms of size-selective fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
166
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(172 citation statements)
references
References 32 publications
(73 reference statements)
4
166
0
1
Order By: Relevance
“…That is, time scales of evolutionary recovery are likely to be much longer than those on which undesirable evolutionary changes occur. Conover et al (101) provided the first experimental test of this expectation with laboratory populations of Menidia menidia. They found that the selective effects of fishing were reversible, but recovery took more than twice as many generations as the original period of fishery selection.…”
Section: Discussionmentioning
confidence: 99%
“…That is, time scales of evolutionary recovery are likely to be much longer than those on which undesirable evolutionary changes occur. Conover et al (101) provided the first experimental test of this expectation with laboratory populations of Menidia menidia. They found that the selective effects of fishing were reversible, but recovery took more than twice as many generations as the original period of fishery selection.…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies on wild fish populations, however, have questioned the notion that larger fish generally exhibit higher reproductive fitness (14,15). As a result, although for many fisheries size-selective exploitation is well established (3)(4)(5)7), there is little empirical evidence from wild populations demonstrating that fishing truly targets reproductively more-fit individuals. One can speculate that certain fishing gear might even target less-fit individuals, that is, those that are either competitively inferior or in poorer condition and therefore more prone to attack fishing lures, more likely to encounter passive fishing gear, or less able to evade actively fished gear such as trawls.…”
mentioning
confidence: 97%
“…It is therefore not surprising that harvesting may cause phenotypic changes in heritable life-history traits in both terrestrial (Allendorf et al, 2008;Coltman et al, 2003) and marine species (Jørgensen et al, 2007). Concerns are mounting about the time it may take to reverse such adaptive changes (Conover et al, 2009;Law and Grey, 1989), if such reversals are feasible at all (de Roos et al, 2006). At this time there is no conclusive genetic evidence of harvesting-induced evolution, however, a growing number of empirical and experimental studies suggest that anthropogenic size-selective mortality in exploited wild populations can cause adaptive changes in traits influencing growth and maturation (Coltman et al, 2003;Jørgensen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%